Effect of ovarian stimulation with recombinant follicle-stimulating hormone, gonadotropin-releasing hormone agonist and antagonists, on follicular fluid stem cell factor and serum urocortin 1 levels on the day of oocyte retrieval - Celik, Onder; Celik, Ebru; Yilmaz, Ercan; Celik, Niluefer; Turkcuoglu, Ilgin; Ulas, Mustafa; Ozerol, Ibrahim (Springer Heidelberg, 2013)
To compare the serum and follicular fluid (FF) concentrations of stem cell factor (SCF) as well as the serum urocortin 1 (UCN1) concentration in gonadotropin-releasing hormone antagonist (GnRH-ant) and gonadotropin-releasing hormone agonist (GnRH-a) protocols for controlled ovarian hyperstimulation (COH) in IVF patients. Follicular fluids and blood samples of 42 infertile women undergoing COH for IVF-embryo transfer with either GnRH agonist (n = 22) or GnRH antagonist (n = 20) protocols from 2010 to 2011 were collected during oocyte retrieval. SCF concentrations of serum and FF were assessed by sandwich enzyme immunoassay using ELISA Kit for SCF kid. Serum UCN1 concentration were measured using commercially available enzyme-linked immunosorbent assay. Concentrations of serum UCN1, serum and FF SCF were similar in the two groups. The serum SCF levels correlated strongly with the follicular SCF levels (r = 0.770, p < 0.001). The mean implantation rate, biochemical and clinical pregnancy rate and live birth rate per cycle were also similar in the groups. These observations suggest that there is no significant difference in follicular microenvironment in terms of SCF and UCN1 between agonist and antagonist protocols.
Keywords: Assisted reproduction; Oocyte maturation; SCF; UCN1; GnRH agonist; GnRH antagonist